Palm oil tocotrienol fractions restore endothelium dependent relaxation in aortic rings of streptozotocin-induced diabetic and spontaneously hypertensive rats - Muharis, S.P.; Top, A.G.M.; Murugan, D.; Mustafa, Mohd Rais (Elsevier, 2010)
Diabetes and hypertension are closely associated with impaired endothelial function. Studies have demonstrated that regular consumption of edible palm oil may reverse endothelial dysfunction. The present study investigates the effect of palm oil fractions: tocotrienol rich fraction (TRF), α-tocopherol and refined palm olein (vitamin E–free fraction) on the vascular relaxation responses in the aortic rings of streptozotocin-induced diabetic and spontaneously hypertensive rats (SHR). We hypothesize that the TRF and α-tocopherol fractions are able to improve endothelial function in both diabetic and hypertensive rat aortic tissue. A 1,1-diphenyl picryl hydrazyl assay was performed on the various palm oil fractions to evaluate their antioxidant activities. Endothelium-dependent (acetylcholine) and endothelium-independent (sodium nitroprusside) relaxations were examined on streptozotocin-induced diabetic and SHR rat aorta following preincubation with the different fractions. In 1-diphenyl picryl hydrazyl antioxidant assay, TRF and α-tocopherol fractions exhibited a similar degree of activity while palm olein exhibited poor activity. TRF and α-tocopherol significantly improved acetylcholine-induced relaxations in both diabetic (TRF, 88.5% ± 4.5%; α-tocopherol, 87.4% ± 3.4%; vehicle, 65.0 ± 1.6%) and SHR aorta (TRF, 72.1% ± 7.9%; α-tocopherol, 69.8% ± 4.0%, vehicle, 51.1% ± 4.7%), while palm olein exhibited no observable effect. These results suggest that TRF and α-tocopherol fractions possess potent antioxidant activities and provide further support to the cardiovascular protective effects of palm oil vitamin E. TRF and α-tocopherol may potentially improve vascular endothelial function in diabetes and hypertension by their sparing effect on endothelium derived nitric oxide bioavailability.